Assessing the relevance of State Capacities for the implementation of public policies by subnational entities (Simbiótica. Revista Eletrônica, 2025)
This paper seeks to verify how the state capacities of Brazilian municipalities interfere with the implementation of cultural public policies in these localities. To this end, theoretical references aligned with the concept of state capacities were used, and variables related to human resources and material and technical infrastructure were operationalized through the R software to assess their influence on the execution of the emergency support policy for culture. Some conclusions indicate the need to apply more variables to determine, with greater precision, the relationship between cause and consequence.
Keywords: Logistic regression; Culture; Municipalities; State Capacities